MERTK Inhibition: Potential as a Treatment Strategy in EGFR Tyrosine Kinase Inhibitor-Resistant Non-Small Cell Lung Cancer - Chen, Chao-Ju; Liu, Yu-Peng (Pharmaceuticals (Basel, Switzerland), 2021)
Epidermal growth factor tyrosine kinase inhibitors (EGFR-TKIs) are currently the most effective treatment for non-small cell lung cancer (NSCLC) patients, who carry primary EGFR mutations. However, the patients eventually develop drug resistance to EGFR-TKIs after approximately one year. In addition to the acquisition of the EGFR T790M mutation, the activation of alternative receptor-mediated signaling pathways is a common mechanism for conferring the insensitivity of EGFR-TKI in NSCLC. Upregulation of the Mer receptor tyrosine kinase (MERTK), which is a member of the Tyro3-Axl-MERTK (TAM) family, is associated with a poor prognosis of many cancers. The binding of specific ligands, such as Gas6 and PROS1, to MERTK activates phosphoinositide 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK) cascades, which are the signaling pathways shared by EGFR. Therefore, the inhibition of MERTK can be considered a new therapeutic strategy for overcoming the resistance of NSCLC to EGFR-targeted agents. Although several small molecules and monoclonal antibodies targeting the TAM family are being developed and have been described to enhance the chemosensitivity and converse the resistance of EGFR-TKI, few have specifically been developed as MERTK inhibitors. The further development and investigation of biomarkers which can accurately predict MERTK activity and the response to MERTK inhibitors and MERTK-specific drugs are vitally important for obtaining appropriate patient stratification and increased benefits in clinical applications.